Remarks in Successful Cellular Investigations for Fighting Breast Cancer Using Novel Synthetic Compounds - Shirazi, Farshad H.; Zarghi, Afshin; Kobarfard, Farzad; Zendehdel, Rezvan; Nakhjavani, Maryam; Arfaiee, Sara; Zebardast, Tannaz; Mohebi, Shohreh; Anjidani, Nassim; Ashtarinezhad, Azadeh; Shoeibi, Shahram (IntechOpen, 2011)
None